Griscelli syndrome: a rare cause of hair and skin hypopigmentation. - Maheshwari, R.; Phiske, M.; Naik, B.; Someshwar, S. (European Journal of Pediatric Dermatology, 2025)
Griscelli Syndrome (GS) is a rare autosomal recessive disorder (approximately 150 cases reported) characterized by light-colored skin and hair, with large clumps of pigment seen in the hair shaft. Three types are distinguished: Type 1, associated with neurological impairment; Type 2, with immunodeficiency; and Type 3, involving only the skin. Of the three subtypes, Types 1 and 3 are rare, with only 27 cases of Type 3 GS reported. Prognosis depends on the presence of neurological (Type 1) or immunological (Type 2) involvement. A 7-year-old child born to non-consanguineous parents presented with multiple hypopigmented macules and patches on the trunk, extremities, and face, present since birth, along with light-colored hair limited to the frontal scalp, with black hair elsewhere – also present since birth. The final diagnosis of Griscelli Syndrome Type 3 was based on clinical and trichoscopic findings, and a normal systemic examination. The unusual feature of this case is the absence of parental consanguinity, previously reported in only two cases in India.